FACTORS INFLUENCING THE IMPROVEMENT OF PROFESSIONAL QUALITY OF GRADUATES OF PROFESSIONAL EDUCATION (Scientific electronic journal "Labor Economics and Human Capital", 2024)
The article considers the issues of ensuring the participation of graduates of vocational education institutions in the labor market by improving their professional qualifications. Practical proposals and recommendations have been developed to ensure the effectiveness of employment of the population in our country, increase the level of employment of broad strata of the working-age population, increase the level of employment of graduates of vocational education institutions, and develop the professional skills of graduates of vocational education institutions.
Keywords: graduates of vocational education, professional skills, employment, working conditions, new jobs, labor market.